Nichos de desenvolvimento infantil: um estudo com mães e educadoras de creche em contexto não urbano - Sousa, Lucivanda Cavalcante Borges de (2016)
The present study targeted at analyzing the niche of infant development inside the familial microsystem and in daycare centers, within a non-urban context. For such, we interviewed 30 mothers and 21 daycare center educators of children aged between 06 and 36 months old, from three non-urban contexts, based on sub-existence agriculture in the city of Petrolina-PE. As theoretical contribution, it was based on the ecocultural perspective of human development, consisting of a complex and dynamic process produced by the individual, and the physical, social, and cultural environment such as interactive systems which make the analysis of the context in which people live indispensable, for each culture and context, in particular, lead to different development processes. We highlight, in this research, the analysis of the niches of infant development in the familial and daycare center microsystems whose environments are comprehended as physical and social, the educational practices, and the parental ethno-theories, taking into account the influences that they have over the child’s development. As tools for this research, we used a socio-demographic questionnaire, a semi-structured interview plan, a structured interview with questions regarding the infant development niches in the familial and daycare center context, and unsystematic observations. The interviews were transcribed and submitted to the content theme analysis, including the material’s exploration and pre-analysis as well as the codification, by using descriptive words and phrases, taking into consideration the criteria for exhaustiveness, representativeness, homogeneity, and pertinence. Later on, the frequency of the mothers’ responses in each category and subcategory was realized, and the average percentage based on the total number of responses obtained in each one of them, calculated. Where the socialization goals are concerned, the responses were also discussed based on the categories as established by Harwood et al., aiming at the understanding of the cultural dimensions highlighted by the participants. Outcomes indicated that mothers, in the majority, show positive conceptions about the child’s development, characterizing them as active, intelligent, and caring, and consider healthcare, affection, and education as relevant factors for infant development; they get involved with ludic interactions toward their children and get concerned with domestic accidents; they use inductive practices in the children’s behavioral control; they set socialization goals turned to the autonomous-relational model and centered strategies as priorities; they expect their children to be able to contribute to society as of the practice of social values; they consider daycare centers as institutions that must promote formal education and the child’s behavioral control. The educators, in turn, pointed education and affection as the main aspects for infant development, built up as of interactive processes; they conceive childhood in a non-urban context as being exposed to danger, and going through affection and economic shortages, leading daycare centers to the duty of giving these children basic needs, stimulating their development, and controlling their behavior. Moreover, they highlight the necessity of a greater partnership between the family and daycare center; they hope the children to achieve socialization goals and societal contributions related to social expectations, followed by autonomy, centralizing the strategies for the achievement of such goals. Results turn out to be discussed as of characteristics of the participants’ eco-cultural context, and considerations by Psychology authors of infant Development.